Hiding in plain sight: immigrant women and domestic violence - Chan, Wendy (Fernwood Publishing, 2020)
"Immigrant women are not only at greater risk of experiencing domestic violence but they also under-utilize mainstream services because their needs are not adequately met there. Understanding their situation involves recognizing that their views and experiences of domestic violence are influenced by the intersections of gender, race, class and immigration. Immigrant women may not access these services because they are unavailable in their community or the women are not aware of the services, or because the services and intervention strategies are not linguistically and culturally appropriate, portable, or coordinated with other services. As a result, the outcomes and solutions provided are often compromised and unsatisfactory. Many immigrant women stay in the abusive relationship, essentially hiding in plain sight, due to the inadequate support available and despite the extraordinary efforts of many service providers. Based on interviews with service providers from the immigration, criminal justice and family justice systems in four different communities in BC, Hiding in Plain Sight examines the barriers encountered by abused immigrant women across Canada as they seek services and support, and identifies the key challenges for abused immigrant women accessing services as well as the struggles service organizations experience in meeting their needs."--